Consumer purchase intention on dietary supplements in Teluk Intan, Perak - Muhammad Arif, Afida Mastura; Mohd Ismail, Nurool Aienna Azwa (Malaysian Association of Consumer and Family Economics, 2024)
The consumption of dietary supplements has been increasing over the years, and it is believed to promote a healthier lifestyle among consumers. This research was undertaken to bridge the gap by establishing the factors that lead to purchase intention on dietary supplements and thus give insights into the marketers to improve health supplement production. A quantitative methodology was employed for this study, and data from 200 respondents were collected using a systematic sampling method. The data were collected through a physical survey and were analyzed using SPSS software. The findings for Pearson correlation has demonstrated that attitude (t=.442**, p=<.001), subjective norm (t=.253**, p=.001), perceived behavioral control (PBC) (t=.350**, p=<.001) and health consciousness (t=.342**, p=<.001) have significant relationship with consumer purchase intention. The study suggested that it is incumbent upon healthcare educators and businesses to assume the responsibility of furnishing consumers with precise and reliable information about the dietary supplement products available in the market.